Retirement Decision of Belgian Couples and the Impact of the Social Security System - Sefane Cetin; Alain Jousten (Institute of Labor Economics (IZA), 2023)
This paper investigates the retirement patterns of married couples in Belgium. To forecast retirement behavior, we use administrative Social Security data from 2003 to 2017 and a discrete choice random utility model. In particular, we concentrate on the spousal bonus of pension payments to comprehend how financial incentives resulting from the social security system's structural design affect both partners' retirement decisions. We simulate the effect of the elimination of the spousal bonus and find that a small portion of women delay their retirement whereas the rest substitute into alternative social security benefits. Our results do not only highlight the significance of cross-program spillovers between various Social Security benefits, but also the heterogeneity in preferences for retirement and asymmetry of retirement behavior between husbands and wives.
Keywords: D10; H55; J26; 330; old-age labor supply; retirement incentives; spousal bonus; pension reforms